A Dictionary of Critical Theory - Buchanan, Ian (Great Clarendon Oxford University Press, 2018)
Boasting more than 750 entries, this is the most wide-ranging and up-to-date dictionary of critical theory available, covering the whole range of critical theory, including the Frankfurt school, cultural materialism, cultural studies, gender studies, film studies, literary theory, hermeneutics, historical materialism, internet studies, sociopolitical critical theory, and much more. Entries clearly explain even the most complex of theoretical discourses, such as Marxism, psychoanalysis, structuralism, deconstruction, and postmodernism. There are biographies of important figures in the field, with feature entries for those who have heavily influenced areas of the discipline. Entries are fully cross-referenced and contain further reading where appropriate. To provide relevant extra information, this edition features recommended web links for many entries, accessible via the Dictionary of Critical Theory companion website, where they are checked regularly and kept up to date. Covering all aspects of the subject from globalization and race studies, to queer theory and feminism, this multidisciplinary A-Z is essential for students of literary and cultural studies and is useful for anyone studying a subject requiring a knowledge of theory.
Keywords: Critical theory